Development and Environmental Resources Conservation - Kaeksi, Retno Woro (Forum Geografi, 1996)
Development is a certain coveted by all people in which included the natural resource development of living members, because a large part of human necessity is supplied by the natural resource. Thus, the more population the more necessities of the natural resource consumed. Natural resource availability is limited while the development is in progress. In such condition the resource is getting decrease and finally destroyed, unless we develop its and make a provision in replacement. Acording to whatÂ  is said by, it is needed a human knowledge about environmental concept of living members in order that in the desired development realization an environmental conservation will be protected permanently.